The Stalin era - Boobbyer, Philip (London : Routledge, 2000)
A wide ranging history of every aspect of Stalin's dictatorship over the peoples of the Soviet Union. It places the man and his ideology into context both within pre-Revolutionary Russia, Lenin's Soviet Union and post-Stalinist Russia.
Preliminaries; Contents; Series editor's preface; Preface; Glossary; Acknowledgements; Notes on the text; 1 Interpreting the Stalin era; 2 From Lenin to Stalin; 3 Collectivisation; 4 Industrialisation; 5 Terror; 6 Government; 7 Stalin The man and the cult; 8 The Second World War; 9 Education and science; 10 The family; 11 Religion The Russian Orthodox Church; 12 The artist and the state; 13 The problem of ends and means; 14 Overview; Bibliography; Index.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Stalin, Josif Vissarionovič -- 1878-1953; Soviet Union -- History -- 1925-1953.; URSS -- Histoire -- 1925-1953.; HISTORY -- Europe -- Russia & the Former Soviet Union; Soviet Union; Sowjetunion; 1925-1953; Electronic books; History